Surface mobility and impact of precursor dosing during atomic layer deposition of platinum: in situ monitoring of nucleation and island growth. Issue 43 (2nd November 2020) - Dendooven, Jolien; Van Daele, Michiel; Solano, Eduardo; Ramachandran, Ranjith K.; Minjauw, Matthias M.; Resta, Andrea; Vlad, Alina; Garreau, Yves; Coati, Alessandro; Portale, Giuseppe; Detavernier, Christophe
Abstract : The nucleation rate and diffusion-driven growth of Pt nanoparticles are revealed with in situ X-ray fluorescence and scattering measurements during ALD: the particle morphology at a certain Pt loading is similar for high and low precursor exposures. Abstract : The increasing interest in atomic layer deposition (ALD) of Pt for the controlled synthesis of supported nanoparticles for catalysis demands an in-depth understanding of the nucleation controlled growth behaviour. We present an in situ investigation of Pt ALD on planar Si substrates, with native SiO2, by means of X-ray fluorescence (XRF) and grazing incidence small-angle X-ray scattering (GISAXS), using a custom-built synchrotron-compatible high-vacuum ALD setup and focusing on the thermal Pt ALD process, comprising (methylcyclopentadienyl)trimethylplatinum (MeCpPtMe3 ) and O2 gas at 300 °C. The evolution in key scattering features provides insights into the growth kinetics of Pt deposits from small nuclei to isolated islands and coalesced worm-like structures. An analysis approach is introduced to extract dynamic information on the average real space parameters, such as Pt cluster shape, size, and spacing. The results indicate a nucleation stage, followed by a diffusion-mediated particle growth regime that is marked by a decrease in average areal density and the formation of laterally elongated Pt clusters. Growth of the Pt nanoparticles is thus not only governed by the adsorption of Pt precursor molecules from the gas-phase and subsequent combustion of the ligands, but is largely determined by adsorption of migrating Pt species on the surface and diffusion-driven particle coalescence. Moreover, the influence of the Pt precursor dose on the particle nucleation and growth is investigated. It is found that the precursor dose influences the deposition rate (number of Pt atoms per cycle), while the particle morphology for a specific Pt loading is independent of the precursor dose used in the ALD process. Our results prove that combining in situ GISAXS and XRF provides an excellent experimental strategy to obtain new fundamental insights about the role of deposition parameters on the morphology of Pt ALD depositions. This knowledge is vital to improve control over the Pt nucleation stage and enable efficient synthesis of supported nanocatalysts.